Systematic calculation of the surface excitation parameters for 22 materials. (4th September 2012) - Da, B.; Sun, Y.; Mao, S. F.; Ding, Z. J.
<x xml:space="preserve">Abstract</x> Quantitative surface analysis requires knowledge of surface excitations by electrons. These excitations are characterized by the surface excitation parameter (SEP) which represents the surface excitation probability while an electron moves across a solid surface. In this work, a systematic calculation of a SEP database has been performed for 22 materials, including metals, oxides and semiconductors, for electron energies between 100 eV and 5000 eV, and for angles α of incidence/emission between 0.5o and 89.5o with respect to the surface normal. Surface excitations are considered for both sides of a solid–vacuum interface when an electron is incident on or emitted from a surface. These SEPs represent not only the appearance of surface excitations but also the inhibition of bulk excitations. Four common SEP formulas are evaluated, and we present best‐fit parameters for the most satisfactory formula. SEP can then be readily determined for about 22 materials and various energies and electron incidence or emission angles. Copyright © 2012 John Wiley & Sons, Ltd.